Knowledge About Child Rearing Practices: Exchange Between Nursery and Family - Bravo-Soto, Astrid Gabriela (2018)
This article presents a case study conducted in Chile. The purpose of this study was to know how the exchange of knowledge on rearing practices occurs between the nursery and families, and how this knowledge is used to enrich the curriculum proposal for the level. Data were collected through document analysis, observation of babies during the workday, and in-depth interviews with the mothers and the staff of the center. Content analysis and triangulation of sources were carried out. The findings show differences in the practices related to the priorities established for each of the contexts, the dynamics that occur in the daily routine, and parameters for judging those differences. Some exchanges are observed concerning feeding practices and the siesta time. It is required to advance in the construction of curricular proposals to rescue families’ knowledge, as well as to broaden the perspective regarding what is selected to be transmitted to the babies.